A bioactive-borate-sealer can protect enamel from erosion during orthodontic treatment. - Clin Prof Mona Aly Abbassy; Professor Ali Habib Hassan; Clin Prof Ahmed Bakry (Elsevier, 2023)
Aim or Purpose: This study tested the ability of a patented borate enamel sealer (BES) (US Patent 11,602,491) to protect enamel surfaces from erosive attack during orthodontic treatment and its effect on shear bond strength (SBS) of orthodontic attachment to enamel treated by (BES). The results were compared to a fluoride agent and a resin sealer. Materials and Methods: 120 human enamel specimens were utilized. Enamel buccal surfaces were etched with phosphoric-acid then divided into: (BES) group; (ERS) resin-adhesive system group; (EF) fluoride gel 1.23% group, and enamel control (EC) group; followed by bonding to orthodontic composite resin attachments. The treated enamel specimens had their (SBS) composite examined utilizing a universal testing machine (Electro Plus E1000, Instron, Canton, MA, USA). The enamel specimens were exposed to 1% citric acid (18 min). Enamel specimens were examined by (SEM/EDS) scanning-electron-microscope equipped with electron-dispersive-spectroscopy and (FTIR/ATR). Analysis-of-Variance (ANOVA) was used to compare the SBS and Wilcoxon-signed-rank test was used to compare the enamel areas protected by the applied agents before/after erosion (p = 0.05). Results: There was no significance difference in SBS among all groups p < 0.05. SEM results showed that (BES) group was the only group that significantly protected enamel from erosion p < 0.05. FTIR/ATR examination showed that erosion did not alter the enamel groups' chemical composition and that Borate enamel sealer has an acceptable "Degree of conversion". Conclusions: The Borate enamel sealer released calcium and phosphate compounds that decreased the erosive activity of the citric acid resulting in protecting enamel from erosion without affecting the SBS to composite Orthodontic attachments.